Implementation of Mutual Cooperation Skills in Pancasila Education Learning in Class 2 of MI Al-Fatih - Fadil, Khaidir; Lik Afifah, Lana; Kamaluddin (Jurnal Evaluasi dan Pembelajaran, 2025)
This study aims to determine the skills of mutual cooperation, the role of teachers in implementing mutual cooperation skills, and also the impact of Pancasila education learning on mutual cooperation skills. By using a descriptive phenomenological research method, the instrument uses interviews, observations and documentation to collect data. The results show that from the 3 data collection techniques, mutual cooperation skills in Pancasila education learning to form and apply positive values to students, the role of teachers is an important role for students as role models, the positive impact of mutual cooperation can develop collaboration in students. In conclusion, this study underlines the importance of incorporating cooperative skills into Pancasila education to build students' ability to work together, the role of teachers who are examples for students in building collaboration, and the positive impact felt by teachers with mutual cooperation, students are able to understand other people's opinions and are active in communicating with their friends. And ensure that students not only learn about these values but also practice them in their daily interactions.